Načrtovanje in izvajanje likovnih dejavnosti v vrtcih - Podobnik, Uršula (Revija za elementarno izobraževanje, 2011)
Planning and Execution of Visual Art Activities in Kindergartens. The following article features the results of a research conducted within a project entitled Professional Training of Expert Staff to Execute Elements of Special Pedagogical Principles of the Reggio Emilia Concept in the Field of Pre-School Education. The research was stimulated and driven by the emphasized role of visual arts in the above mentioned pedagogical concept, and the analysis of pre-school visual arts practice in Slovenian kindergartens. The theoretical part of the article introduces characteristics of quality visual arts activities in pre-school period and presents various organisational possibilities which ought to be included in planning and execution of visual arts activities. These starting points served as guidelines for the empirical part, where we primarily focused on the factors which are often emphasized by the Reggio Emilia experts. A questionnaire was set to explore the methods of planning and execution of visual arts activities in the pre-school period in our environment. In the interpretative part of the article we focused on the comparison of kindergarten teachers’ work in urban, suburban and rural environments, and tried to establish how great the influence of a kindergarten’s placement in the environment was. Furthermore, we tried to shed light on different modification possibilities of planning visual arts activities with respect to kindergarten’s placement in a certain environment.
Keywords: pre-school education; visual arts in the pre-school period; planning visual arts activities; execution of visual arts activities